Nanotechnology boosts the efficiency of tumor diagnosis and therapy - Yang, Ying; Lin, Mali; Sun, Mengfan; Zhang, Guo-Qiang; Guo, Jianshuang; Li, Jianheng (Frontiers in Bioengineering and Biotechnology, 2023)
The incidence and mortality of cancer are gradually increasing. The highly invasive and metastasis of tumor cells increase the difficulty of diagnosis and treatment, so people pay more and more attention to the diagnosis and treatment of cancer. Conventional treatment methods, including surgery, radiotherapy and chemotherapy, are difficult to eliminate tumor cells completely. And the emergence of nanotechnology has boosted the efficiency of tumor diagnosis and therapy. Herein, the research progress of nanotechnology used for tumor diagnosis and treatment is reviewed, and the emerging detection technology and the application of nanodrugs in clinic are summarized and prospected. The first part refers to the application of different nanomaterials for imaging in vivo and detection in vitro, which includes magnetic resonance imaging, fluorescence imaging, photoacoustic imaging and biomarker detection. The distinctive physical and chemical advantages of nanomaterials can improve the detection sensitivity and accuracy to achieve tumor detection in early stage. The second part is about the nanodrug used in clinic for tumor treatment. Nanomaterials have been widely used as drug carriers, including the albumin paclitaxel, liposome drugs, mRNA-LNP, protein nanocages, micelles, membrane nanocomplexes, microspheres et al, which could improve the drug accumulate in tumor tissue through enhanced permeability and retention effect to kill tumor cells with high efficiency. But